Improving chemical learning outcomes with explicit instruction learning models with quizizz evaluation media - Bropson Minanlarat; Leony Sanga Lamsari Purba; St Fatimah Azzahra (Jurnal Pendidikan Kimia (JPKim), 2021)
This study aims to determine the effect of explicit instruction learning models and the percentage of student learning outcomes improvement in chemistry. Explicit instruction learning model is the free variable while the dependent variable is learning outcomes. This research method is a quasi experiment with the research design nonequivalent control group design. The population of this study were students of Senior High School 42 Jakarta, the sample was selected by purposive sampling technique, consisting of two classes, namely class XI MIA 1 as the experimental class and XI MIA 2 as the control class. The results of the ttest show that the sig. (2-tailed) is smaller than the α value, namely sig 0.000 < sig 0.05, so learning using the explicit instruction model has a significant effect on improving chemistry learning outcomes on hydrocarbon compound material. In addition, the use of explicit instruction learning models can improve student learning outcomes by 19% when compared with the use of conventional learning models (TCL).Keywords: Explicit instruction, Quizizz, Chemistry learning, Learning outcomes